Pathoepidemiology of Cervical Cancer in National Institute of Cancer Research and Hospital of Bangladesh - Jabeen, Suraiya; Islam, Md Johirul; Talukder, Md Habibullah; Nurunnabi, Abu Sadat Mohammad; Haque, Musarrat (Journal of Dhaka Medical College, 2015)
A study was conducted to find out the descriptive epidemiological and pathological characteristics among the incidental cases of cervical cancer patients attending National Institute of Cancer Research & Hospital (NICRH), Dhaka, Bangladesh, during January to December, 2012. In this hospital based case-control study 278 patients with histologically, cytopathologically or by the oncologists confirmed cervical cancer were compared with equal number of controls, who had cancers other then cervical, form the same hospital. The mean ages for the cervical cancer cases were 44.90±7.217 years. The morphological categorization of the cervical cancer patients was squamous cell carcinoma (93%) and rest adenocarcinoma (7%). The majority of cases presented with moderately differentiated or grade 2 lesions (45.9%). There were no in-situ cases. Almost all the cancers cases (90.9%) had regional lymph node involvement. Odds ratios (OR) and 95% confidence intervals (CI) were obtained from multivariate logistic regression analysis. Compared with controls, it was found that cases having higher education (OR=1.46, 95% CI: 1.35-6.42), more personal income (OR=0.129, 95% CI: .02-.24), small family size (OR=0.018, 95% CI: 27.88-120.95) had a decreased risk for cervical cancer. However, marital status (OR=1.97, 95% CI: 4.21-20.69), age at marriage (OR=2.57, 95% CI: 11.45-118.29), age at 1st child (OR=9.33, 95% CI: 0.14-0.65), had more risk for cervical cancer. This study concludes that the majority of the cervical cancer sufferers at NICRH were from lower- socioeconomic group having less education with a late cancer presentation mostly with squamous cell carcinoma. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 203-210